2017
DOI: 10.1016/j.chemosphere.2017.05.098
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol and snow transfer processes: An investigation on the behavior of water-soluble organic compounds and ionic species

Abstract: h i g h l i g h t sThe air-snow transfer processes were evaluated using water soluble compounds. This is the first study about amino acids and sugar concentration in surface snow. Water soluble organic fractions of Antarctic aerosol and snow were investigated. a r t i c l e i n f o b s t r a c tThe concentrations of water-soluble compounds (ions, carboxylic acids, amino acids, sugars, phenolic compounds) in aerosol and snow have been determined at the coastal Italian base "Mario Zucchelli" (Antarctica) during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 48 publications
0
12
0
1
Order By: Relevance
“…Recently, Barbaro et al. (2017) found a higher abundance of phenolic compounds in surface snow as well as aerosols in the coastal Italian base station of the Antarctic during austral summer. Of all these studies, we suggest that the formation of unsaturated diacids is possibly associated with the photooxidation of phenolic compounds that are enriched in sea‐surface microlayer over the Antarctic.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Barbaro et al. (2017) found a higher abundance of phenolic compounds in surface snow as well as aerosols in the coastal Italian base station of the Antarctic during austral summer. Of all these studies, we suggest that the formation of unsaturated diacids is possibly associated with the photooxidation of phenolic compounds that are enriched in sea‐surface microlayer over the Antarctic.…”
Section: Resultsmentioning
confidence: 99%
“…A significant amount of phthalates are also reported over the biologically active marine aerosols over the marine boundary layer (Bikkina et al, 2015) and also at a remote marine island (Boreddy et al, 2017) under the trade wind regimes over the western North Pacific. Recently, Barbaro et al (2017) found a higher abundance of phenolic compounds in surface snow as well as aerosols in the coastal Italian base station of the Antarctic during austral summer. Of all these studies, we suggest that the formation of unsaturated diacids is possibly associated with the photooxidation of phenolic compounds that are enriched in sea-surface microlayer over the Antarctic.…”
Section: Unsaturated and Multifunctional Diacidsmentioning
confidence: 99%
“…The aliphatic region ( Figures 5, S8) exhibits broad similarity to that of the primary marine particles generated in the sea spray tank, but with a major difference in the chemical shift range between 1.7 and 3.0 ppm where the background broad NMR bands are much more intense in the ambient sample. This is also the region recovering the signals from acyl groups (RCH-(C=O)-) in aliphatic carboxylic acids and ketoacids, which are formed by VOC oxidation in the atmosphere (Barbaro et al, 2017). The most abundant individual compounds detected in these samples https://doi.org/10.5194/acp-2019-888 Preprint.…”
Section: Ambient Aerosols From the Weddell Seamentioning
confidence: 99%
“…(Rintoul et al;. As all these specific ecosystem impacts involve factors deemed important for aerosol production in Antarctica (Davison et al, 2006;Schmale et al, 2013;Kyrö et al, 2013;Barbaro et al 2017), a significant effect of climate change on atmospheric concentrations of aerosols and cloud condensation nuclei (CCN) must be expected to occur by the end of this century. The field studies performed in maritime and coastal areas around Antarctica in the austral summer since the 90's (Davison et al, 1996) enable us to gather precious information on the multiple feedbacks between atmospheric composition and ecosystems in a warming climate.…”
Section: Introductionmentioning
confidence: 99%
“…Besides being crucial for glacier mass balance, the annual snowpack is a sink and a reservoir for a wide range of inorganic and organic elements naturally present and/or released by human activities. The presence of impurities in the annual snowpack, in the form of either insoluble dust particles (Barbante et al, 2017), soluble chemical species (Barbaro et al, 2017b) or organic compounds (Vecchiato et al, 2018), can be used to study the transport processes from polluted source areas at mid-latitudes and constrain the potential impact of human activities on the Arctic environment (Barbante et al, 2001;Ezerinskis et al, 2014;Nawrot et al, 2016).…”
Section: Introductionmentioning
confidence: 99%